GAMBARAN PERAN KELUARGA DALAM MERAWAT PASIEN DENGAN GANGGUAN PERSEPSI SENSORI : HALUSINASI DI POLIKLINIK JIWA UPTD. RUMAH SAKIT JIWA PROVINSI BALI - I.W Edi Parjana; N. M. S Muryani; I. W Suarjaya (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2019)
Background: Hallucinations are one of the mental disorders in which the client experiences sensory changes in perception, feels a false sensation in one's senses which is not really there. The family is the closest person to the patient's family role that can be carried out by family to family members who experience hallucinations is to help clients know hallucinations and train clients to control their hallucinations. Objective: The purpose of this study was to describe the role of families in treating patients with sensory perception disorders: hallucinations. Results: The results of the study were obtained in fulfilling the patient's self-care who had a good role, namely 7 (21.9%) family members, patient health care as many as 7 (21.9%) family members, prevention of potential patient accidents as many as 8 (25 , 0%) family members and were prevented from withdrawing from the environment as many as 11 (34.4%) family members who received patients with hallucinations. Conclusions: conclusions were obtained as many as 6 (18.8%) family members who play a good role in caring for patients with hallucinations. 26 (81.3%) family members did not play a good role in caring for family members with hallucinations.Keywords: Role of family; hallucinations